Novejši nemški dvojezični slovarji za slovenske uporabnike - Hočevar, Mojca M. (Mostovi (Ljubljana), 2006)
In the article, three recently issued German-Slovene bilingual dictionaries for Slovene users are presented: the transliteral edition of Pleteršnik's Slovene-German Dictionary, The German General Dictionary: German-Slovene, Slovene-German, and The PONS General German-Slovene Dictionary.
Keywords: nemščina; Nemški splošni slovar; ocene in poročila; Pleteršnik, Maks: Slovensko-nemški slovar; slovarji; slovenščina; Splošni nemško-slovenski slovar